Nilai-nilai Tarbiyah Ibadah Kurban dan Relevansinya dengan Pembelajaran Pendidikan Formal - Muhammad Alqadri Burga; Andi Marjuni; Rosdiana Rosdiana (LP2M STIT Palapa Nusantara, 2019)
This research analyzes the values of Islamic education in the history of kurban worship according to QS al-Ṣaffāt/37: 100-108 and its relevance to formal education. The type of research used is qualitative with text study method. Data is collected through documentation and then analyzed using the content analysis method. The results of the research show that the history of kurban worship according to QS al-Ṣaffāt/37: 100-108 is divided into four episodes: (1) expectations, (2) examinations, (3) pass the exam, and (4) awards. The values of Islamic education found in kurban worship ere eight: (1) faith, (2) morals, (3) patience, (4) resignation, (5) sincerity, (6) democratic, (7) dialogue, and (8) social. The values of Islamic education in the history of kurban worship has relevance to the main characteristics of learning design and the learning process which consists of planning, implementation, evaluation, and follow-up. In addition, it accommodates all values ​​that will be developed in character education.